O DESAFIO DA ALFABETIZAÇÃO: O MÉTODO E SUAS IMPLICAÇÕES TEÓRICO- TÉCNICAS. - Andréa Henrique Franco Bertan; Lucia Helena Tiosso Moretti (Universidade do Oeste Paulista, 2005)
The objective of this paper was to analyze the literacy along the Pedagogical Political Projects (PPP) of two schools of a city of north Parana State. The focus was on investigating the problems that involve the literacy process: theories, methodologies and the applications of the PPP. The methodology used to develop this study was through Case Study. It involved a public and a private school, so that could be compared the methodologies and the theories applied in the literacy practice and the analysis of PPP from each school. The sample was compounded by four teachers from the public school and one from the private one, all of them teaching in the first grade of Fundamental level. The interviews were individual so the teachers could feel free to answer without any interruptions. The observations were made twice a week through the analysis of the methodologies used in class and the relation with the PPP of each school. They revealed the coherences and incoherences of the work in literacy teaching, and how much these practices are or not lined with the pedagogical propose of the PPP from each school.